Establishing relationship between process parameters and temperature during high speed end milling of soda lime glass - Bagum, Mst. Nasima; Konneh, Mohamed; Ali, Mohammad Yeakub (Institute of Physics Publishing, 2018)
In glass machining crack free surface is required in biomedical and optical industry. Ductile mode machining allows materials removal from brittle materials in a ductile manner rather than by brittle fracture. Although end milling is a versatile process, it has not been applied frequently for machining soda lime glass. Soda lime glass is a strain rate and temperature sensitive material; especially around glass transition temperature Tg, ductility increased and strength decreased. Hence, it is envisaged that the generated temperature by high-speed end milling (HSEM) could be brought close to the glass transition temperature, which promote ductile machining. In this research, the objective is to investigate the effect of high speed machining parameters on generated temperature. The cutting parameters were optimized to generate temperature around glass transition temperature of soda lime using response surface methodology (RSM). Result showed that the most influencing process parameter is feed rate followed by spindle speed and depth of cut to generate temperature. Confirmation test showed that combination of spindle speed 30,173 rpm, feed rate 13.2 mm/min and depth of cut 37.68 μm generate 635°C, hence ductile chip removal with machined surface Ra 0.358 μm was possible to achieve.